Online Technology and Business Performance of SMEs In Osun State (UNIZIK Journal of Marketing, 2024)
Businesses are shifting from conventional methods of purchasing and selling to adopting online technology platforms due to advancements that enhance business performance. Despite the significant advantages of Internet technology in business, trade, industry, and commerce, many small and medium-sized business owners in Nigeria have yet to fully embrace the Internet's limitless benefits in their operations. This research, therefore, investigates the influence of online payment integration on SMEs' performance and examines the role of social media in enhancing the business performance of SMEs in the Osogbo Metropolis. Questionnaires were distributed to SMEs in Osogbo, with a sample size of 250. The descriptive statistical method employed included a frequency distribution table and simple percentages, while the stated hypothesis was tested using multiple linear regression.  The findings indicate that the adoption of online technology has effectively improved SMEs' operations and performance, enhanced their methods of operation, and enabled them to expand across markets. Social media and online payment integration continue to play a crucial role in the performance of many SMEs' online technology strategies. Additional data analysis reveals that business performance increases by 0.394 and 0.295 for every unit increase in social media and online payment integration, respectively. Furthermore, online marketing has significantly improved SMEs' performance through enhanced social media platform marketing. It is recommended that SMEs utilize service providers offering bundled packages that include internet access, software, and support services at a reduced cost.
Keywords: Online Technology; SMEs Positioning; SMEs Performance; Social Media, Communication